Thai Politics: The Transition and Transformation - Vansu, Roostum; Pinyasin, Natsit (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2019)
The challenges of democracy among Southeast Asian countries and the disruption of democracy in Thailand, particularly in the recent Thai coup d'état in 2014, are undoubtedly the reasons for continued interest in the politics of Thailand. It is gratifying to have the chance to reflect on the continuing validity of the assessment several years later and ask whether the trends that seemed to dominate five years ago are still so today. This study focuses on Thai politics in the transition and transformation period since General Prayut Chan-o-cha took power in 2014 and following Thailand's 2019 election that General Prayu Chan-o-cha returned for a second term as Prime Minister. This study offers data on the political context of Thailand, Dictatorship Democracy in Thailand, democratic development and challenge in Thailand's politics, authoritarianism and hybrid democracy in Southeast Asia, and the 2019 Thai election results and the future of Thailand's politics. For everyone in society, the political situation is influential as the transition and transformation in government policy is essential information as people can approach and adapt to the new information update and deal with the new situation in the near future.